Effects of Zaï Pit Depth on Morphological Traits, Yield Components and Yield of Cowpea (Vigna unguiculata (L.) Walp) in Burkina Faso - (:unkn) unknown (My University, 2023)
Cowpea is the leading food legume for many households in arid and semi-arid regions of Sub-Saharan Africa. The erratic rainfall leads to decrease in cowpea yield. The Zaï pit technology is an ancestral agricultural technique used for water and fertilizer management in crops production increasing productivity. A study was carried out in Burkina Faso during 2020 and 2021 dry season at Kamboinsin and at Kouare with for objective of evaluating the effects of Zaï depth on cowpea yield and yield components. Treatments consisted of the use of three Zaï depths (control (tillage); 15 cm; 25 cm) and four cowpea varieties. The experimental design used was a split-plot replicated three times. Yield and yield components data were collected and subjected to an analysis of variance using JMP Pro 10 software. The results showed that for all the studied varieties, all the yield components and yields average values increased with the Zaï pit depth. Zaï of 25 cm and 15 cm depth increased cowpea grain yield of more than 87% and 50% respectively compared to the control (tillage). Twenty-five-centimetre Zaï depth substantially enhances cowpea agronomical performances and is recommendable for cowpea production in drought prone regions or of low rainfall.
Keywords: African Research